Production of FAME from acid oil model using immobilized Candida antarctica lipase - Watanabe, Yomi; Pinsirodom, Praphan; Nagao, Toshihiro; Kobayashi, Takashi; Nishida, Yutaka; Takagi, Yoshiaki; Shimada, Yuji (My University, 2005)
Acid oil is a by-product in the neutralization step of vegetable oil refining and is an alternative source of biodiesel fuel. A model substrate of acid oil, which is composed of TAG and FFA, was used in experiments on the conversion to FAME by immobilized Candida antarctica lipase. FFA in the mixture of TAG/FFA were efficiently esterified with methanol (MeOH), but the water generated by the esterification significantly inhibited methanolysis of TAG. We thus attempted to convert a mixture of TAG/FFA to FAME by a two-step process comprising methyl esterification of FFA and methanolysis of TAG by immobilized C. antarctica lipase. The first reaction was conducted at 30°C in a mixture of TAG/FFA (1:1, wt/wt) and 10 wt% MeOH using 0.5 wt% immobilized lipase, resulting in efficient esterification of FFA. The reaction mixture after 24 h was composed of 49.1 wt% TAG, 1.3 wt% FFA, 49.1 wt% FAME, and negligible amounts of DAG and MAG (<0.5 wt%). The reaction mixture was then dehydrated and used as a substrate for the second reaction, which was conducted at 30°C in a solution of the dehydrated mixture and 5.5 wt% MeOH using 6 wt% immobilized lipase. The activity of the lipase increased gradually when the reaction was repeated by transferring the enzyme to a fresh substrate mixture. The activity reached a maximum after 6 cycles, and the content of FAME achieved was >98.5 wt% after a 24-h reaction. The immobilized lipase was very stable in the first- and second-step reactions and could be used for >100 d without significant loss of activity. Copyright © 2005 by AOCS Press.
Keywords: Acid oil; Biodiesel fuel; Candida antarctica; FAME; Immobilized enzyme; Lipase; Methanolysis; Methyl esterification